Pengaruh Zakat Terhadap Pertumbuhan Ekonomi dengan Tingkat Kemiskinan sebagai Variabel Intervening - Zulaika Matondang; Hamni Fadlilah Nasution (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2026)
The optimal distribution of zakat has the potential to improve community welfare by stimulating economic activities and contributing to poverty alleviation, thereby supporting economic growth. Although zakat collection in Indonesia has shown an increasing trend, economic growth has tended to decline, while poverty levels have remained relatively high. This study aims to examine the effect of zakat on economic growth with poverty serving as a mediating variable in Indonesia. This study employed a quantitative research approach using panel data regression analysis. The research utilized data from eight provinces in Indonesia covering the period from 2018 to 2024. The findings indicate that zakat has a significant effect on economic growth and poverty levels. Poverty also has a significant effect on economic growth. However, poverty does not mediate the relationship between zakat and economic growth. These findings suggest that while zakat directly contributes to economic growth and poverty reduction, its indirect effect on economic growth through poverty is not statistically significant.